Intoxicating followership : in the Jonestown Massacre - Edmonds, Wendy M. (Emerald Publishing Limited, 2021)
Toxic behavior is on the rise in public safety organizations, businesses, politics, and churches, to name a few. Faced with unprecedented circumstances, there is a need to better understand leader/follower interdependence when destructive leaders are at the helm making harmful decisions. Toxic followership begins with the pioneering spirit of a trusted individual who, through creative manipulation, transforms our mindset whereby we can so easily become an extension of a toxic leader's moral decay. There is a myth that the Jonestown tragedy is a distant episode in history that can only happen in certain environments with people unlike oneself. The survivor's stories are reminders that without understanding the framework of toxic followership, the unsuspecting targets are prey, available for consumption by a leader with liquidated morals. This book is for those who desire to gain insight into the leader/follower dynamic in order to serve others by unmasking the dangers of toxic followership, provide prevention suggestions, and reveal followers' power, even in desperate situations.
Includes index.
Keywords: Followership.; Leadership.; Jonestown Mass Suicide, Jonestown, Guyana, 1978.; Social Science -- Disease & Health Issues.; Social, group or collective psychology.; elektronické knihy; electronic books